Growth Opportunity and Firm Value in Indonesian Manufacturing Firms - Sugeng Haryanto; Sunardi Sunardi; Eko Ariestanto; Prihat Assih; Adi Suroso; Zaenal Aripin (AFRE (Accounting and Financial Review), 2022)
This study aims to analyze the effect of investment decisions, funding decisions, dividend decisions on firm value and whether growth opportunity affects the relationship between investment policy, funding policy and dividend policy on firm value. This research was conducted on a manufacturing company that went public on the Indonesia Stock Exchange. The number of samples in the study was 92 companies with a research period of 2015-2020 so that the amount of data analysis was 552. The data analysis technique used moderated regression analysis (MRA). The results of the study found that investment decisions have a negative effect on firm value. While funding decisions, dividend decisions have a positive effect on firm value. Growth opportunity is able to strengthen the influence of investment decisions on firm value. Growth opportunities weaken funding and dividend decisions. The results of this study indicate that growth opportunity is important information for investors, because it will be related to the sustainability and prospects of the company in the future.DOI: https://doi.org/10.26905/afr.v5i3.8936